2011
DOI: 10.5402/2011/271209
|View full text |Cite
|
Sign up to set email alerts
|

Cooccurrence of Yawning and Stereotypic Behaviour in Horses (Equus caballus)

Abstract: Determinants of yawning are still uncertain. As yawning seems to be triggered by stress and emotional contexts, we investigated specific correlates of yawning and stereotypic behaviours in horses. Study 1 investigated correlations in time between yawning and stereotypic behaviour in stereotypic horses from the same facility; study 2, involving riding school horses, investigated the cooccurrence of yawning and stereotypic behaviour at the individual level and in response to environmental factors (feeding time).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
1
4

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 28 publications
(59 reference statements)
5
45
1
4
Order By: Relevance
“…In animals, lions and mandrills yawned most when inactive but awake (Baenninger, 1987), and yawning rate correlated positively with stereotypic performance in horses (Fureix, Gorecka-Bruzda, Gautier, & Hausberger, 2011), both of which are consistent with boredom, but other explanations cannot be ruled out.…”
Section: Nfmentioning
confidence: 82%
“…In animals, lions and mandrills yawned most when inactive but awake (Baenninger, 1987), and yawning rate correlated positively with stereotypic performance in horses (Fureix, Gorecka-Bruzda, Gautier, & Hausberger, 2011), both of which are consistent with boredom, but other explanations cannot be ruled out.…”
Section: Nfmentioning
confidence: 82%
“…The increase of excitement due to the anticipation of food or reward arrival is well known to increase the rate of STB in horses but also locomotor play in piglets (Dudink, Simonse, Marks, de Jonge & Spruijt, 2006). In a study on horses, Fureix et al (2011) showed a co-occurrence between yawning and STB: The rates were correlated in some populations of horses, but could also just occur mostly in the same circumstances such as the pre-feeding period or periods without roughage. These findings do not lead to causal explanations, but provide hints about common factors of causation (e.g., frustration in this case).…”
Section: Stereotypic Behavior and Adult Play: A Co-occurrence In Primmentioning
confidence: 99%
“…Earlier studies have tried to relate derived activities with STB in primates (Reamer, Tooze, Coulson, & Semple, 2010) or in other mammals (Fureix, Gorecka-Bruzda, Gautier, & Hausberger, 2011) or have based the assessment of stress on activities such as self-scratching (Norscia & Palagi, 2011). Mancini and Palagi (2009) found that play behavior and allogrooming were more frequent in the pre-feeding periods and concluded that play may be used to release tensions in such situations that are characterized by conflicts of interest.…”
Section: Stereotypic Behavior and Adult Play: A Co-occurrence In Primmentioning
confidence: 99%
“…Displacement yawning is broadly recognized to increase with anxiety or social conflict in primates (e.g., Macaca nigra, Hadidian, 1980;M. mulatta, Graves and Wallen, 2006;Pan troglodytes, Vick and Paukner, 2010) but has also been observed in other species including non-mammals, e.g., ostriches (Struthio camelus, Sauer and Sauer, 1967), dogs (Buttner and Strasser, 2014), fish (Microspathodon chrysurus, Rasa, 1971), and horses (Fureix et al, 2011). In horses, the frequency of yawning correlates positively with the performance of stereotypic behavior (Fureix et al, 2011).…”
Section: Can Facial Expression Indicate Negative Affective States?mentioning
confidence: 99%
“…Pain will be examined in a separate section due to its specific, well-defined contribution to poor welfare states, as well as the comparatively large body of literature on facial indicators of pain. In mammals, facial expressions have been extensively Cabanac and Lafrance, 1990Spotila et al, 1977Wells, 1978;Robertshaw, 2006Gaughwin, 1979Stahlbaum and Houpt, 1989;Weeks et al, 2002;Charpentier et al, 2013Fox, 1970Sandem and Braastad, 2005;Kaiser et al, 2006;Bennett et al, 2012 Sefcek andKing, 2007;Knierim et al, 2007Partan, 2002Parr et al, 2005Parr et al, , 2007Bethell et al, 2012 Baker andAureli, 1997;Sandem et al, 2002;De Marco et al, 2010;Vick and Paukner, 2010Nagasawa et al, 2013Redbo, 1998Mason et al, 2007;Fernandez et al, 2008;Mason, 2010;Fureix et al, 2011;Tan et al, 2013Fox, 1970Waller and Dunbar, 2005;Judge and Bachmann, 2013;Yanagi andBerman, 2014 Craig et al, 1991;Langford et al, 2010;Sotocinal et al, 2011;Leach et al, 2012;Dalla Costa et al, 2014;Wathan et al, 2015;McLennan et al, 2...…”
mentioning
confidence: 99%